Creating a vibrant city center : urban design and regeneration principles - Paumier, Cyril B. (Washington, D.C. : Urban Land Institute, 2004)
What makes a city great? This book reveals the key planning and design guidelines needed to create a lively, appealing city center in any metropolitan area.
1. Historical perspective -- 2. Regeneration principles -- 3. Market components -- 4. Importance of place -- 5. Place principles -- 6. Public spaces -- 7. Pedestrian realm -- 8. Vehicular circulation -- 9. Public transit -- 10. Parking facilities -- 11. Development guidelines -- 12. Planning guidelines -- 13. Visioning process -- 14. Development plan -- 15. Plan implementation.
Keywords: City planning; Central business districts; Urban renewal